Cave tourism in Switzerland: The assessment and implications for subterranean geoheritage sustainability - Antić Aleksandar; Luetscher Marc; Perret Amandine; Ferrando Andrea; Reynard Emmanuel (Moravian Geographical Reports)
This study explores the significance of show caves as subterranean geoheritage sites, focusing on their potential for sustainable cave tourism. The primary objective is to comprehensively assess caves, considering speleological, infrastructure, and tourist values, while developing sustainable tourism strategies. For this, a novel methodology was created that involves literature review, field surveys, assessments and stakeholder consultations, which is applied in the evaluation of nine show caves in Switzerland. By addressing potential challenges and negative impacts, we analyze current tourism development and propose mitigation strategies. Combining quantitative and qualitative analyses, including geological, ecological, and cultural factors, the study offers a comprehensive evaluation, contributing a practical methodology for cave management, as well as cave tourism planning. The findings provide insights beyond academia, guiding stakeholders involved in cave tourism development, and striving to balance ecosystem preservation with sustainable economic growth.